Identification of a highly efficient dual type I/II FMS-like tyrosine kinase inhibitor that disrupts the growth of leukemic cells. Issue 3 (17th March 2022) - Beyer, Mandy; Henninger, Sven J.; Haehnel, Patricia S.; Mustafa, Al-Hassan M.; Gurdal, Ece; Schubert, Bastian; Christmann, Markus; Sellmer, Andreas; Mahboobi, Siavosh; Drube, Sebastian; Sippl, Wolfgang; Kindler, Thomas; et al.
Summary: Internal tandem duplications (ITDs) in the FMS-like tyrosine kinase-3 (FLT3) are causally linked to acute myeloid leukemia (AML) with poor prognosis. Available FLT3 inhibitors (FLT3i) preferentially target inactive or active conformations of FLT3. Moreover, they co-target kinases for normal hematopoiesis, are vulnerable to therapy-associated tyrosine kinase domain (TKD) FLT3 mutants, or lack low nanomolar activity. We show that the tyrosine kinase inhibitor marbotinib suppresses the phosphorylation of FLT3-ITD and the growth of permanent and primary AML cells with FLT3-ITD. This also applies to leukemic cells carrying FLT3-ITD/TKD mutants that confer resistance to clinically used FLT3i. Marbotinib shows high selectivity for FLT3 and alters signaling, reminiscent of genetic elimination of FLT3-ITD. Molecular docking shows that marbotinib fits in opposite orientations into inactive and active conformations of FLT3. The water-soluble marbotinib-carbamate significantly prolongs survival of mice with FLT3-driven leukemia. Marbotinib is a nanomolar next-generation FLT3i that represents a hybrid inhibitory principle. Graphical abstract: Highlights: Marbotinib is a nanomolar and specific next-generation FLT3i Marbotinib inhibits FLT3-ITD and FLT3-ITD/TKD mutations as a double-edged sword TKi Marbotinib inhibits the growth of permanent and primary AML cells Water-soluble marbotinib-carbamate prolongs survival of mice with FLT3-driven leukemia Abstract : Beyer et al., characterize the highly selective and specific FLT3 inhibitor marbotinib and its water-soluble derivate. These agents suppress the phosphorylation of hyperactive FLT3 and the growth of permanent and primary AML cells with FLT3-ITD and FLT3-ITD/TKD mutants. Marbotinib binds inactive and active conformations of FLT3 in opposite orientations.